Role of erythropoietin in methotrexate-induced nephrotoxicity in adult male albino rats - Ahmed Hassan Al-Rashidy; Rasha Rabea Salem; Amal Abdelrasool Alhosary; Mohamed Hassan Wahdan; Gamal Mohamed Elnemr; Khalid Ebraheem Hassan; Atif Ibrahim Ali (Society of Diabetic Nephropathy Prevention, 2018)
Introduction: Methotrexate (MTX) could provoke a renal dysfunction. However, beneficial extra-hematopoietic effect of erythropoietin might guard against MTX-induced nephrotoxicity. Objectives: Determination of renoprotective erythropoietin's role against MTX-induced nephrotoxicity through elucidating its renofunctional and renomorphological effects in adult male albino rats. Materials and Methods: The study was performed on 60 adult male Albino rats, equally divided into three groups; group 1 (control): treated with intraperitoneal injections of normal saline at a dosage of 0.5 mg/kg BW twice weekly for 9 weeks. group 2: injected with MTX hydrate intraperitoneal twice weekly at a dosage of 0.5 mg/kg BW for 9 weeks; and group 3: intraperitoneal injected with MTX hydrate in a similar dosage and duration like group 2 concomitant with subcutaneous injection of 100 IU/kg recombinant human erythropoietin once weekly for 9 weeks. At the study end, serum urea and creatinine together with albuminuria were measured, rats were sacrificed and renal sections were prepared for histopathological examination. Results: Significantly increased values of renal function analyzed substances with deteriorated histopathological renal changes were detected in the MTX-treated group compared to either the control or to the MTX and erythropoietin co-treated group. The later displayed statistically significant decreased levels of the substances accompanied by remarkably ameliorated microscopic renal changes. Additionally, insignificant statistical biochemical and morphological renal differences were noticed between the third and control groups. Conclusion: This study concluded valuable and efficient defense against MTX-induced nephrotoxicity in adult male Albino rats when co-treated with erythropoietin.